2019
DOI: 10.1038/s41598-019-51356-w
|View full text |Cite
|
Sign up to set email alerts
|

LTA1 is a safe, intranasal enterotoxin-based adjuvant that improves vaccine protection against influenza in young, old and B-cell-depleted (μMT) mice

Abstract: Enterotoxin-based adjuvants including cholera toxin and heat-labile toxin (LT) are powerful manipulators of mucosal immunity; however, past clinical trials identified unacceptable neurological toxicity when LT or mutant AB5 adjuvant proteins were added to intranasal vaccines. Here, we examined the isolated enzymatic A1 domain of LT (LTA1) for intranasal safety and efficacy in combination with influenza (flu) vaccination. LTA1-treated mice exhibited no neurotoxicity, as measured by olfactory system testing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Notably, low numbers of neutrophils were noted in mice receiving nasal immunization with PspA, together with Alcaligenes lipid A under uninfected conditions (Figure 7), suggesting that the recruitment of neutrophils seem to be mediated by antigen-specific immune responses, but not non-specific activation by lipid A, which was different phenotype from CT. We found that CT induced the accumulation of neutrophils in the nose under uninfected conditions, indicating that CT induced non-specific inflammation upon nasal administration. Consistent with this finding, it has been shown that CT induces inflammatory responses, including neutrophil infiltration into subepithelial tissues of nasopharynx cavity [59,60], and E. coli lipid A enhanced inflammatory cytokines, such as TNFα and IL-1β [61]. These findings suggest that Alcaligenes lipid A possesses higher levels of safety as a nasal vaccine adjuvant, compared with the classical mucosal adjuvant: CT and immuno-stimulatory component: E. coli lipid A.…”
Section: Discussionsupporting
confidence: 55%
“…Notably, low numbers of neutrophils were noted in mice receiving nasal immunization with PspA, together with Alcaligenes lipid A under uninfected conditions (Figure 7), suggesting that the recruitment of neutrophils seem to be mediated by antigen-specific immune responses, but not non-specific activation by lipid A, which was different phenotype from CT. We found that CT induced the accumulation of neutrophils in the nose under uninfected conditions, indicating that CT induced non-specific inflammation upon nasal administration. Consistent with this finding, it has been shown that CT induces inflammatory responses, including neutrophil infiltration into subepithelial tissues of nasopharynx cavity [59,60], and E. coli lipid A enhanced inflammatory cytokines, such as TNFα and IL-1β [61]. These findings suggest that Alcaligenes lipid A possesses higher levels of safety as a nasal vaccine adjuvant, compared with the classical mucosal adjuvant: CT and immuno-stimulatory component: E. coli lipid A.…”
Section: Discussionsupporting
confidence: 55%
“…The cause of this neurotoxic effects were thought to be the combination of binding of de B subunit of LT to surface gangliosides (especially GM1) and inflammation associated with the A subunit. However, the use of the enzymatic A1 domain was shown to be safe and effective 52 .…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, Tamura et al found that the CT B subunit (CTB) could significantly increase IN TIV-induced cross-protection against a drifted virus in murine models, while subcutaneous delivery of the same vaccine failed to induce similar levels of cross-protection [ 149 ]. An LT-adjuvanted influenza vaccine was approved for IN delivery in Switzerland (Nasalflu, Berna Biotech) during the 2000-2001 flu season [ 174 ]. However, it was pulled off the market due to the 19-fold increased risks of Bell’s palsy or facial paralysis in vaccine recipients [ 174 ].…”
Section: Vaccine Adjuvants Assist Influenza Vaccines To Induce Cromentioning
confidence: 99%
“…An LT-adjuvanted influenza vaccine was approved for IN delivery in Switzerland (Nasalflu, Berna Biotech) during the 2000-2001 flu season [ 174 ]. However, it was pulled off the market due to the 19-fold increased risks of Bell’s palsy or facial paralysis in vaccine recipients [ 174 ]. Therefore, different LT mutants were developed to reduce the enterotoxicity of LT-based adjuvants, such as single-mutant LT (R192G) and double-mutant LT (R192G/L211A) [ 175 , 176 ].…”
Section: Vaccine Adjuvants Assist Influenza Vaccines To Induce Cromentioning
confidence: 99%